Role of ketamine in treatment-resistant depression - Dmochowska, Joanna; Ciechański, Marcin; Cieszkowska, Joanna; Czerwik , Julia; Czubala, Marta; Felisiak, Patrycja; Gąska, Wiktor; Kanon, Karol; Witkowska, Edyta (Journal of Education, Health and Sport, 2025)
Introduction: Depression, affecting 350 million people globally, is a leading cause of disability. Common symptoms include low mood, sadness, guilt, anxiety, and suicidalthoughts. Current treatments, mostly monoamine-based antidepressants, have limitations such as delayed effects and low efficacy, with over 60% of patients not achieving lasting remission. Ketamine, an NMDA antagonist, has shown rapid antidepressant effects, and research suggests glutamatergic dysfunction plays a role in TRD, highlighting the need for faster, more effective treatments. Current state of knowledge: Ketamine, an NMDA receptor antagonist, has gained attention for its rapid antidepressant effects, particularly in treatment-resistant depression. It works by modulating the glutamatergic system, enhancing synaptic plasticity, and involving other systems like GABA and 5-HT. Clinical trials have shown ketamine’s efficacy in reducing depressive symptoms and suicidal ideation within hours, contrasting with traditional antidepressants that take weeks. The intravenous route is most effective, with lower bioavailability in other forms. While ketamine shows promise, its potential for addiction and side effects necessitate careful monitoring. Conclusion: Evidence supports ketamine for treating refractory depression, enhancing neuroplasticity and regulating affective symptoms through anti-inflammatory effects. Variations exist in administration route, bioavailability, and patient age. Common adverse effects include dissociative symptoms and cardiovascular issues, requiring careful monitoring and management.